Soil C and N dynamics in a Mediterranean oak woodland with shrub encroachment - Gómez-Rey, Maria Xesús; Madeira, Manuel; Gonzalez-Prieto, Serafin Jesús; Coutinho, João (Plant and Soil, 2013)
Background and aims Intensive land use has led to degradation and abandonment of Portuguese oak woodlands, and subsequent shrub encroachment may have altered the spatial heterogeneity of soil C and N pools. The aim of this study was to evaluate the effects of shrub invasion on soil C and N dynamics in an oak woodland in Southern Portugal. Methods Soil was sampled beneath and outside scat- tered Quercus suber L. canopies, considering non- encroached areas and areas encroached by shrubs (Cistus ladanifer L. or Cistus salviifolius L.). Results The spatial heterogeneity of soil C and N contents was mainly associated with tree presence. Outside tree canopies, the labile C pools were larger (mainly beneath C. ladanifer) and C cycling was faster in encroached areas than in non-encroached areas. Net and gross N mineralization and urease and protease activities were also higher in encroached than in non- encroached areas; however, the metabolic quotient and the Cmicrobial/Corganic ratio were not significantly affected. Beneath the tree canopy, significant effects of encroachment included a small increase in soil labile C and the enzymatic activity beneath C. ladanifer. Conclusions The results indicate the potential capaci- ty of shrub encroachment to accumulate soil organic C in the long term. The rate of soil C and N turnover promoted by shrub encroachment may depend on the Cistus species present.
Keywords: 15 N isotope dilution technique; gross N mineralization; hot water-soluble C; particulate organic matter; Soil respiration